Chromosomal principle of radiation-induced F1 sterility in Ephestia kuehniella (Lepidoptera: Pyralidae) - Tothová, A; Marec, F (Genome, 2001)
A dose-response analysis of chromosomal aberrations was performed in male progeny of gamma-irradiated males in the flour moth, Ephestia kuehniella. For comparison, several female progeny from each dose level were examined. Aberrations were detected on microspread preparations of pachytene nuclei in the electron microscope and classified according to pairing configurations of synaptonemal complexes (SCs). Fragmentation and various translocations were the most numerous aberrations, whereas interstitial deletion and inversion were rare. At 100 Gy, relatively simple multiple translocations were found. Multiple translocations showing complicated configurations occurred at 150 and 200 Gy, and their number increased with the dose. In males, the mean number of chromosomal breaks resulting in aberrations linearly increased with the dose from 8.4 to 16.2 per nucleus. In females, this value achieved a maximum of 11.2 breaks/nucleus at 200 Gy. Three factors were suggested to contribute to the reported higher level of F1 sterility in males than females: (i) survival of males with high numbers of breaks, (ii) crossing-over in spermatogenesis but not in the achiasmatic oogenesis, and (iii) a higher impact of induced changes on the fertility of males than females. It was concluded that translocations are most responsible for the production of unbalanced gametes resulting in sterility of F1 moths. However, F1 sterility predicted according to the observed frequency of aberrations was much higher than the actual sterility reported earlier. This suggests a regulation factor which corrects the predicted unbalanced state towards balanced segregation of translocated chromosomes.
Keywords: infertilita; Infertility; Male; chromozomy; Sex Characteristics; Crosses, Genetic; můry; chromozomální aberace; translokace genetická; mužské pohlaví; pohlavní dimorfismus; Gamma Rays; elektronová mikroskopie; Chromosome Aberrations; Dose-Response Relationship, Radiation; Animals; křížení genetické; ženské pohlaví; Chromosomes; tolerance záření; zvířata; Microscopy, Electron; Translocation, Genetic; Radiation Tolerance; vztah dávky záření a odpovědi; Female; záření gama; Moths